Molecular cloning of plane pollen allergen Pla a 3 and its utility as diagnostic marker for peach associated plane pollen allergy. Issue 5 (May 2016) - Wangorsch, A.; Larsson, H.; Messmer, M.; García‐Moral, A.; Lauer, I.; Wolfheimer, S.; Schülke, S.; Bartra, J.; Vieths, S.; Lidholm, J.; Scheurer, S.
Summary: Background: Non‐specific lipid transfer proteins (nsLTP) are considered to provoke allergic symptoms to plane tree pollen, which are frequently associated with peach allergy. Objective: The objective was to clone the cDNA of plane pollen nsLTP Pla a 3, to characterize IgE‐binding and allergenic potency of recombinant Pla a 3 in comparison to its natural counterpart and peach nsLTP Pru p 3. Methods: Natural Pla a 3 was purified from plane pollen and analysed by mass spectrometry (MS). Recombinant Pla a 3 was characterized by SDS‐PAGE and CD spectroscopy. Specific IgE to extract, components of plane pollen and Pru p 3 was measured by ImmunoCAP in sera of patients allergic to either plane pollen ( n  = 10), peach ( n  = 15) or both ( n  = 15). Biological potency of the proteins was investigated by in vitro mediator release assays and IgE cross‐reactivity by competitive ELISA. Results: Two Pla a 3 isoforms were identified. Recombinant Pla a 3 showed high purity, structural integrity, IgE‐binding capacity comparable to nPla a 3 and biological potency. Sensitization to plane pollen extract was confirmed in 24/25 plane pollen allergics. The frequency of sensitization to Pla a 3 was 53% among patients allergic to both plane pollen and peach and 10% among plane pollen allergics tolerating peach where most patients were sensitized to Pla a 1. Pla a 3 and Pru p 3 showed strong bi‐directional IgE cross‐reactivity in patients allergic to peach and plane pollen, but not in peach allergics tolerating plane pollen. Levels of IgE‐binding were generally higher to Pru p 3 than to Pla a 3. Conclusion: Sensitization to Pla a 3 is relevant in a subgroup of plane pollen allergics with concomitant peach allergy. IgE testing with Pla a 3 may serve as a marker to identify plane pollen allergic patients at risk of LTP‐mediated food reactions and thereby improve in vitro diagnostic procedures.